INSTITUTIONS THAT MATCH UP SAVERS AND BORROWERS HELP ENSURE THAT ECONOMIES FUNCTION SMOOTHLY. - JO’RAYEVA ZEBO (Лучшие интеллектуальные исследования, 2024)
You have got 1,000 you don’t need for, say, a year and want to earn income from the money until then. Or you want to buy a house and need to borrow 100,000 and pay it back over 30 years. It would be difficult, if not impossible, for someone acting alone to find either a potential borrower who needs exactly 1,000 for a year or a lender who can spare 100,000 for 30. That’s where banks come in.